Kiprah Suryani Thahir dalam Pemberdayaan Perempuan Betawi melalui Majelis Taklim (1970–2006) - Muhammad Rafli Zakaria; Achmad Maftuh Sujana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article examines the role and contributions of Ustadzah Suryani Thahir in empowering Betawi women through Majelis Taklim (Islamic study groups) in South Jakarta between 1970 and 2006. The study employs historical research methodology, consisting of five main stages: topic selection, heuristics, verification, interpretation, and historiography. Primary sources were obtained through interviews with the subject’s family members and authentic written documents, while secondary sources were collected through literature review. The findings reveal that Suryani Thahir played a dual role as both a religious preacher and a social mobilizer, actively guiding women in religious, educational, and self-development matters. The Majelis Taklim she led served as a strategic platform for Betawi women to gain religious knowledge and expand their social roles amid the dynamics of an urban society. This study highlights the significance of local female figures in the socio-religious history of Jakarta, particularly in elevating the position of women in public spaces through cultural and religious approaches.